The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/brainsci12020194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motor Imagery Tasks on Brain Functional Networks Based on EEG Mu/Beta Rhythm

Abstract: Motor imagery (MI) refers to the mental rehearsal of movement in the absence of overt motor action, which can activate or inhibit cortical excitability. EEG mu/beta oscillations recorded over the human motor cortex have been shown to be consistently suppressed during both the imagination and performance of movements, although the specific effect on brain function remains to be confirmed. In this study, Granger causality (GC) was used to construct the brain functional network of subjects during motor imagery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…A popular topic in analyzing EEG is during motor imagery (MI) tasks, which are dynamic states of movement imagination during which primary sensorimotor areas exhibit patterns of neural activity that resembles an attenuated version of real executed movement [2,3]. From neurophysiological perspective, desynchronization of the neural populations during motor imagery tasks attenuates rhythms in the respective cortex and can be measured as a sign of brain activity [3,4]. MI tasks are extensively utilized in brain-computer interface (BCI) systems, in which mental imagination of a movement is translated to executive commands via classification of features extracted from acquired EEG data [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A popular topic in analyzing EEG is during motor imagery (MI) tasks, which are dynamic states of movement imagination during which primary sensorimotor areas exhibit patterns of neural activity that resembles an attenuated version of real executed movement [2,3]. From neurophysiological perspective, desynchronization of the neural populations during motor imagery tasks attenuates rhythms in the respective cortex and can be measured as a sign of brain activity [3,4]. MI tasks are extensively utilized in brain-computer interface (BCI) systems, in which mental imagination of a movement is translated to executive commands via classification of features extracted from acquired EEG data [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have found the motor mental practice can provide several benefits in patients with neurological disorders ( Kim and Lee, 2015 ; Gil-Bermejo-Bernardez-Zerpa et al, 2021 ). Changes in the functional network induced by motor imagery may contribute to the recovery from brain dysfunction ( Bajaj et al, 2015 ; Yu et al, 2022 ). Especially, imaging motors have been reported to have similar patterns of brain activity to real execution ( Kraeutner et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frontal regions are involved in the processing of MI, and they may be differentially responsive ( Buch et al, 2012 ; Yu et al, 2022 ). The current study adds to this literature that all frontal regions were shown differently between groups while demonstrating greater activation in stroke with the impaired MI ability compared with that of healthy controls.…”
Section: Discussionmentioning
confidence: 99%